2018
DOI: 10.1038/s41467-018-05248-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of atom motion and metal deposition in mixed ionic electronic conductors

Abstract: Many superionic mixed ionic–electronic conductors with a liquid-like sublattice have been identified as high efficiency thermoelectric materials, but their applications are limited due to the possibility of decomposition when subjected to high electronic currents and large temperature gradients. Here, through systematically investigating electromigration in copper sulfide/selenide thermoelectric materials, we reveal the mechanism for atom migration and deposition based on a critical chemical potential differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
165
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 29 publications
4
165
0
1
Order By: Relevance
“…Copyright 2014, Wiley‐VCH. b) Critical electric current density ( J c ) and c) critical electric potential difference ( V c ) of Cu 1.97 S as a function of the L material . d) Relative electrical resistance variation ( R/R 0 , R is the concurrent electrical resistance and R 0 is the initial electrical resistance) as a function of J for Cu 2 Se and Cu 2− x S ( x = 0, 0.03, 0.04, 0.06, and 0.1) legs with the material length ( L material ) of 10 mm …”
Section: Device and Challengementioning
confidence: 99%
See 3 more Smart Citations
“…Copyright 2014, Wiley‐VCH. b) Critical electric current density ( J c ) and c) critical electric potential difference ( V c ) of Cu 1.97 S as a function of the L material . d) Relative electrical resistance variation ( R/R 0 , R is the concurrent electrical resistance and R 0 is the initial electrical resistance) as a function of J for Cu 2 Se and Cu 2− x S ( x = 0, 0.03, 0.04, 0.06, and 0.1) legs with the material length ( L material ) of 10 mm …”
Section: Device and Challengementioning
confidence: 99%
“…Qiu et al developed a theoretical model to investigate the diffusion of Cu ions in the superionic α‐phase of Cu 2 X and the corresponding . Historically, it is believed that the critical parameter of Cu protrusion in Cu 2 X is the electric current density ( J ).…”
Section: Device and Challengementioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, we have studied the mechanism of Cu migration in liquidlike materials and found it is possible to greatly improve material's stability by introducing electronically-conducting but ion-blocking barriers [104]. Similarly, Tang et al [105] found that the incorporated graphene three dimensional (3D) network can provide another possibility to block the migration of Cu ions and to enhance the stability of Cu 2 S.…”
Section: Concerns About Cu Migration and Materials Stabilitymentioning
confidence: 99%